Herod: king of the Jews and friend of the Romans - Richardson, Peter (Routledge ancient biographies, 2018)
"Herod examines the life of this controversial figure, the most highly visible of the Roman client kings under Augustus, whose rule shaped the world in which Christianity arose. In this expanded second edition, additions include discussion of the archaeological evidence of Herod's activity, his building program, numismatic evidence, and consideration of the roles and activities of other client kings, making this a valuable tool for those interested in the wider Roman world of the late first century BCE. With new maps, architectural drawings, and numerous photographs, Herod remains the definitive study of the life and activities of the king known traditionally as Herod the Great."--Provided by publisher